Cytological screening for cervical cancer and associated factors in the penitentiary population of Peru - JC Ruiz-Maza; RA Soto-Azpilcueta; J Sanchez-Salvatierra; Y Torres-Prado (Revista Española de Sanidad Penitenciaria)
ABSTRACT Objective To determine the prevalence and factors associated with the screening of cervical cancer by Papanicolaou in the penitentiary population of Peru. Method A cross-sectional study was conducted using data from the 2016 National Penitentiary Population Census of Peru. The dependent variable was the cytological screening of cervical cancer during the last year. The independent variables were classified as facilitators, sociodemographic predisposers, and generators of need for the use of health services. The multivariate association was estimated through adjusted prevalence ratios (aPR) and 95% confidence intervals (95% CI), using Poisson regression and using the variables with p <0.05 in the bivariate. Results A total of 4515 women incarcerated in the 67 prisons of Peru entered the study. 69% (95% CI: 67.81-70.5) performed cytological screening during the last year and this is associated with having public health insurance (aPR 1.28 , 95% CI: 1.21-1.36), go to prison health services (aPR 1.18 , 95% CI: 1.12-1.24) and have a history of cancer (aPR 1.14, 95% CI: 1.02-1.26). Age, number of children, sports activities and the type of prison were also associated with cytological screening. Discussion There is an association between cytological screening and access to health services, sociodemographic predispositions and pathological backgrounds of women incarcerated in Peru. More research should be promoted on health prevention behaviors in this population.